Environmentally Friendly and Roll-Processed Flexible Organic Solar Cells Based on PM6:Y6 - Fernández-Castro, Marcial; Truer, Jean; Espindola-Rodriguez, Moises; Andreasen, Jens Wenzel (Frontiers in Nanotechnology, 2022)
Organic Solar Cells (OSCs) have reached the highest efficiencies using lab-scale device manufacturing on active areas far below 0.1 cm2. The most used fabrication technique is spin-coating, which has poor potential for upscaling and substantial material waste. This tends to widen the so-called “lab-to-fab gap”, which is one of the most important challenges to make OSCs competitive. Other techniques such as blade or slot-die coating are much more suitable for roll-to-roll manufacturing, which is one of the advantages the technology presents due to the huge potential for fast and low-cost fabrication of flexible OSCs. However, only a few studies report solar cells using these fabrication techniques, especially applied on a roll-platform. Additionally, for environmentally friendly large area OSCs, inks based on non-hazardous solvent systems are needed. In this work, slot-die coating has been chosen to coat a PM6:Y6 active layer, using o-xylene, a more environmentally friendly alternative than halogenated solvents, and without additives. The optimal coating process is defined through fine-tuning of the coating parameters, such as the drying temperature and solution concentration. Moreover, ternary devices with PCBM, and fully printed devices are also fabricated. Power conversion efficiencies of 6.3% and 7.2% are achieved for binary PM6:Y6 and ternary PM6:Y6:PCBM devices measured with an aperture area of 0.4 cm2 (total device area 0.8 cm2) .